Causalidad psíquica y lazo social contemporáneo (2010)
ABSTRACT: On INSERM’s report «Behavioral Disorders in Children and Adolescents» mental causation is reduced to bio- logical causation, symptoms are reduced to disorders, and the psychic is reduced to the behavioral. This report makes human phenomena so abstract that it ends proposing that actions are not performed by ac- tive subjects. This article questions this deterministic position; and following Psychoanalysis ideas about subjectivity it shows the importance of language and words on mental causation.